2009
DOI: 10.1007/s11270-009-0203-9
|View full text |Cite
|
Sign up to set email alerts
|

Use of Fast Repetition Rate Fluorometry on Detection and Assessment of PAH Toxicity on Microalgae

Abstract: Cultures of the flagellate Isochrysis galbana were used to carry out the ecotoxicological evaluation of four PAHs [(naphthalene, phenanthrene, pyrene (Pyr) and fluoranthene (Flu)] by monitoring growth rate and the fluorescence variables F 0 , F m , F v and F v /F m , determined with a fast repetition rate fluorometer. The results presented in this investigation showed that F v was a suitable endpoint in acute ecotoxicological tests with marine phytoplankton. The derived effective concentrations followed the kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Wang et al (2008) reported the growth of the eukaryotic alga diatom Phaeodactylum tricornutum was significantly inhibited under 0.1 mg/L pyrene stress. Photosynthesis of the eukaryotic flagellate Isochrysis galbana was also significantly inhibited at 0.12 mg/L pyrene (Pérez et al, 2009). In our study, there was no inhibition effect on photosynthesis and growth (data not shown) at 0.125 mg/L pyrene.…”
Section: Discussionmentioning
confidence: 97%
“…Wang et al (2008) reported the growth of the eukaryotic alga diatom Phaeodactylum tricornutum was significantly inhibited under 0.1 mg/L pyrene stress. Photosynthesis of the eukaryotic flagellate Isochrysis galbana was also significantly inhibited at 0.12 mg/L pyrene (Pérez et al, 2009). In our study, there was no inhibition effect on photosynthesis and growth (data not shown) at 0.125 mg/L pyrene.…”
Section: Discussionmentioning
confidence: 97%
“…Sensitivity for specific families of pollutants was not observed, and each species showed different behaviors with respect to the three groups of compounds. It must be underlined that the differences in the response of microorganisms to the same or to similar pollutants may depend on various factors, ranging from lipid peroxidation to metabolic energy deficiency, decreased photosynthetic energy, or endocrine disrupting effects, and are therefore species-specific and related to the ecology and physiology of the organism [67]. Except for benzenesulphonamides, the freshwater alga, in particular, and the diatomea seemed to be the most sensitive to these compounds, not only concerning the degree of growth inhibition produced by the high concentration, but mainly with respect to the response to the lowest ones.…”
Section: Discussionmentioning
confidence: 99%
“…Chlorophyll fluorescence-based estimation of microalgal photosynthetic variables in toxicity assays usually relies on whole suspension measurements that obscure differences among individual cells. The sub-lethal effects of PAHs on marine phytoplankton photosynthesis are well documented, both at population and community levels (Pérez et al, 2010). However, the mechanism of PAH toxicity in phytoplankton photosynthesis remains ambiguous because different species show contrasting photosynthetic responses (Ben Othman et al, 2018;Othman et al, 2012).…”
Section: Discussionmentioning
confidence: 99%